A GUCY2D variant associated cone-rod dystrophy with electronegative ERG: A case report and review - Pei-Liang Wu; Pei-Hsuan Lin; Winston Lee; Ethan Hung-Hsi Wang; Eugene Yu-Chuan Kang; Laura Liu; Nan-Kai Wang (American Journal of Ophthalmology Case Reports)
Purpose: Cone-rod dystrophies (CORD) are inherited retinal dystrophies characterized by primary cone degeneration with secondary rod involvement. We report two patients from the same family with a dominant variant in the guanylate cyclase 2D (GUCY2D) gene with different phenotypes in the electroretinogram (ERG). Observations: A 21-year-old lady (Patient 1) was referred due to experiencing blurry vision and color vision impairment. Visual field testing revealed a central scotoma. Spectral-domain optical coherence tomography (SD-OCT) and fundus autofluorescence (FAF) documented macula dysfunction. Reduced amplitude was observed in the photopic responses of ERG. Her 54-year-old father (Patient 2) had similar issues with blurry vision. A dilated fundus examination displayed bilateral macular atrophy. Loss of the ellipsoid zone line and collapse of the outer nuclear segment were noted on the SD-OCT. Photopic ERG responses were extinguished, and an electronegative ERG was observed in the dark-adapted 3.0 ERG. The gene report revealed a c.2512C > T (p.Arg838Cys) variant in GUCY2D for both patients. They were respectively diagnosed as cone dystrophy (COD) and cone-rod dystrophy (CORD). Conclusions: We report two different clinical phenotypes in GUCY2D-associated COD despite sharing the same variant. A dysfunction in the synaptic junction between the photoreceptor and the secondary neuron was proposed to explain the electronegative ERG. This explanation might extend to other gene-related cases of CORD with electronegative ERG.